2003
DOI: 10.1136/adc.88.6.520
|View full text |Cite
|
Sign up to set email alerts
|

Hypoparathyroidism and 22q11 deletion syndrome

Abstract: Aims: To investigate a population of individuals with 22q11 deletion syndrome for hypocalcaemia. Methods: A detailed clinical history enquiring into symptoms of hypocalcaemia and blood sampling to assess for hypocalcaemia and hypoparathyroidism, of patients outside the neonatal period known to have the 22q11 microdeletion from fluorescent in situ hybridisation studies was taken. Results: Sixty one individuals were identified, of whom 23 were untraceable and one was unable to give informed consent. Biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 9 publications
2
44
1
7
Order By: Relevance
“…The inability to increase PTH secretion appropriate for hypocalcemic stimulus can be demonstrated with a provocative test using disodium edetate infusion (8,19). It is suggested that families with 22q11 syndrome should be informed of the symptoms that might occur with hypocalcemia (20). Moreover, screening of abnormal parathyroid function should be considered in the regular follow-up of patients with del(22)(q11) (21).…”
Section: Discussionmentioning
confidence: 99%
“…The inability to increase PTH secretion appropriate for hypocalcemic stimulus can be demonstrated with a provocative test using disodium edetate infusion (8,19). It is suggested that families with 22q11 syndrome should be informed of the symptoms that might occur with hypocalcemia (20). Moreover, screening of abnormal parathyroid function should be considered in the regular follow-up of patients with del(22)(q11) (21).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hypoparathyroidism typically manifests with hypocalcemia (1), with 22q11.2 deletion syndrome being recognized as its major cause (2). This syndrome, which includes DiGeorge syndrome and velocardiofacial syndrome, is caused by microdeletion of chromosome region 22q 11.2 (3).…”
Section: Introductionmentioning
confidence: 99%
“…This syndrome, which includes DiGeorge syndrome and velocardiofacial syndrome, is caused by microdeletion of chromosome region 22q 11.2 (3). It is associated with a typical facial appearance and clinical symptoms and findings such as congenital heart defects, immune deficiency caused by thymic hypoplasia, palatal cleft and mental retardation (2,4,5). In addition, autoimmunity is more common in affected patients than in the general population (6).…”
Section: Introductionmentioning
confidence: 99%
“…Гипопаратиреоз с/без симптоматической гипо-кальциемии (50-65% пациентов с 22q11.2DS), заболе-вания щитовидной железы с гипо-или гиперфункцией, дефицит гормона роста, внутриутробная задержка роста (около 4% пациентов), невысокий рост -основные проявления при del 22q11.2 [37][38][39]. Гипопаратиреоз с гипокальциемией обнаруживается у 50-65% пациен-тов с 22q11.2DS [40,41].…”
Section: эндокринные нарушенияunclassified